Two Neutral White Illumination Loci Based on Unique White Rating and Degree of Chromatic Adaptation. Issue 2 (3rd April 2018) - Smet, Kevin A. G.
ABSTRACT: In this article, two new neutral loci are presented characterizing the whiteness perception of illumination color of on- and off-Planckian light sources. The two neutral loci are derived based on (1) unique white ratings obtained on a real three-dimensional cube (UW-locus, object mode based) and (2) the degrees of adaptation obtained from a study of chromatic adaptation under neutral and highly colored illuminations (CA-locus, illumination mode based). Equations are presented describing the loci in the CIE u ′ v ′ chromaticity diagram and in terms of distance from the Planckian locus (Duv) versus correlated color temperature (CCT) and of "degree of neutrality" versus CCT. Although the two neutral loci are very similar in shape, they are not identical, with the UW-locus being approximately a (blue) shifted version of the CA-locus. The latter was in very good agreement with other illumination based neutral white loci reported in the literature, which all have in common negative Duv for lower CCTs and positive Duv for higher CCTs. Like several other lines of white and achromatic points from literature, the UW-neutral locus was located completely below the Planckian locus. The chromaticity associated with the maximum degree of neutrality was for both loci very close to that of the CIE D65 daylight illuminant, suggestive of earlier reports that vision processes such as color constancy and chromatic adaptation, and hence perceived illumination neutrality, are likely conditioned by natural scene statistics.